Multiscale hierarchical bioresorbable scaffolds for the regeneration of tendons and ligaments. (12th June 2019) - Sensini, Alberto; Gualandi, Chiara; Focarete, Maria Letizia; Belcari, Juri; Zucchelli, Andrea; Boyle, Liam; Reilly, Gwendolen C; Kao, Alexander P; Tozzi, Gianluca; Cristofolini, Luca
Abstract: Lesions of tendons and ligaments account for over 40% of the musculoskeletal lesions. Surgical techniques and materials for repair and regeneration are currently not satisfactory. The high rate of post-operative complications and failures mainly relates to the technical difficulties in replicating the complex multiscale hierarchical structure and the mechanical properties of the native tendons and ligaments. With the aim of overcoming the limitations of non-biomimetic devices, we developed a hierarchical structure replicating the organization of tendons and ligaments. The scaffold consists of multiple bundles made of resorbable electrospun nanofibers of Poly-L-Lactic acid (PLLA) having tailored dimensions, wrapped in a sheath of nanofibers able to compact the construct. The bundles in turn consist of electrospun nanofibers with a preferential direction. High-resolution x-ray tomographic investigation at nanometer resolution confirmed that the morphology of the single bundles and of the entire scaffold replicated the hierarchical arrangement in the natural tendons and ligaments. To confirm that these structures could adequately restore tendons and ligaments, we measured the tensile stiffness, strength and toughness. The mechanical properties were in the range required to replace and repair tendons and ligaments. Furthermore, human fibroblasts were able to attach to the scaffolds and showed an increase in cell number, indicated by an increase in metabolic activity over time. Fibroblasts were preferentially aligned along the electrospun nanofibers. These encouraging in vitro results open the way for the next steps towards in vivo regeneration of tendons and ligaments.